699. Relationship Between Klebsiella pneumoniae Antimicrobial Resistance and Biofilm Formation. (26th November 2018) - Cusumano, Jaclyn; Daffinee, Kathryn; Luther, Megan; Lopes, Vrishali; Caffrey, Aisling; LaPlante, Kerry
Abstract: Background: Klebsiella pneumoniae is a frequently multidrug-resistant organism with a high propensity to form biofilm. K. pneumoniae is the most common carbapenem-resistant Enterobacteriaceae (CRE), and labeled an urgent threat by the CDC. The relationship between K. pneumoniae biofilm formation and specific antimicrobial resistance patterns has not been well defined. Methods: K. pneumoniae isolates ( n = 139) were evaluated for antimicrobial resistance and biofilm formation (CDC, Providence VA Med. Ctr., Rhode Island Hosp., BEI, and ATCC). Susceptibility was based predominantly on 2017 CLSI (Clinical and Laboratory Standards Institute) breakpoints. Isolates were categorized as multidrug-resistant (MDR: resistant to ≥ 1 antimicrobial in ≥ 3 out of 16 antimicrobial categories) or extensively drug-resistant (XDR: resistant to ≥ 1 antimicrobial in all but ≤ 2 out of 16 antimicrobial categories) based on expert consensus criteria for Enterobacteriaceae (European CDC (ECDC)/CDC, 2012). We collapsed antimicrobial categories described by the ECDC/CDC consensus group into nine categories: penicillins, cephalosporins, monobactam, carbapenems, protein synthesis inhibitors, fluoroquinolones, folate pathway inhibitors, fosfomycin, and colistin. Biofilm formation was assessed using a modified crystal violet method (OD570 ) and defined by tertile cut-points. Antimicrobial resistance was compared for weak ( n = 47) vs. strong ( n = 46) biofilm formation by chi-square or Fisher's exact test. Predictors of strong biofilm formation were identified using logistic regression. Results: MDR isolates were more common among weak ( n = 46/47, 97.9%) vs. strong biofilm formers ( n = 35/46, 76.1%; P = 0.002), whereas XDR was similar between groups ( n = 12/47, 25.5% vs. n = 13/46, 28.3% P = 0.77). Resistance to penicillins, cephalosporins, monobactams, carbapenems, protein synthesis, or fluoroquinolones was more common among weak biofilm formers ( P < 0.05). Carbapenem resistance was inversely associated with strong biofilm formation (odds ratio 0.09; 95% confidence interval 0.02–0.33). Conclusion: Carbapenem-resistant K. pneumoniae was 91% less likely to form strong biofilm. Potential trade-off mechanisms between antimicrobial resistance and biofilm formation require further exploration. Disclosures: A. Caffrey, Merck: Grant Investigator, Research grant. The Medicine's Company: Grant Investigator, Research grant. Pfizer: Grant Investigator, Research grant. K. LaPlante, Merck: Grant Investigator, Research grant. Pfizer Pharmaceuticals: Grant Investigator, Research grant. Allergan: Scientific Advisor, Honorarium. Ocean Spray Cranberries, Inc.: Grant Investigator and Scientific Advisor, Honorarium and Research grant. Achaogen, Inc.: Scientific Advisor, Honorarium. Zavante Therapeutics, Inc.: Scientific Advisor, Honorarium.